Citizen participation in the formulation of local public policies, the case of district VI of the Municipality of Managua (2007-2013) - Morales, Rodolfo (Journal Studies of Public Policy, 2016)
This study case analyzes the processes of citizen participation in the formulation of local policies and interrelationships of citizenship with the District VI of the municipality of Managua, in the period 2007-2013. Specifically, it discusses how the new model for citizen participation (``Gabinetes de la Familia, la Comunidad y la Vida’’), implemented by Presidential Decree 112 -2007, works and is operationalized, and how it contributes to designs local public policies. This research corresponds to a single case and was developed from a qualitative descriptive approach. A participatory process that is built from the territorial bases, with a relatively young and evolving organization, which functions as a hinge mechanism and institutional management to bring public services to the needs of communities is observed. The contribution of citizen participation and the idea of a relational government, involving the citizens in decisions is recognized. However, despite the involvement of citizens in social issues, this is still in the level of information and consultation, as the community work like facilitators of information and inputs, so the government can make the best decision.